Hierarchical mesoporous octahedral K2Mn1−xCoxFe(CN)6 as a superior cathode material for sodium-ion batteries. Issue 41 (6th October 2016) - Jiang, Xiaolei; Liu, Hongjin; Song, Jie; Yin, Changfang; Xu, Huayun
Abstract : A new Prussian blue analogue, hierarchical mesoporous octahedral K2 Mn1− x Co x Fe(CN)6 ( x = 0, 0.05, 0.1 and 0.2), has been successfully synthesized for the first time via a simple magnetically stirred process. Abstract : A new Prussian blue analogue, hierarchical mesoporous octahedral K2 Mn1− x Co x Fe(CN)6 ( x = 0, 0.05, 0.1 and 0.2), has been successfully synthesized for the first time via a simple magnetically stirred process. K2 Mn1− x Co x Fe(CN)6 ( x = 0, 0.05, 0.1 and 0.2) was selected as a cathode material for sodium ion batteries to increase their lattice parameters, along with the large available tunnels for Na + diffusion. We also introduce cobalt into the framework to stabilize the crystal structure and improve the electronic conductivity of the KMHFC particles. These composites are characterized via powder X-ray diffractometry, and scanning and transmission electron microscopy. Among the samples, K2 Mn0.9 Co0.1 Fe(CN)6 exhibits the best electrochemical performance as a cathode material for sodium ion batteries, with a discharge capacity of 116 mA h g −1 after 150 cycles at 10 mA g −1 . This superior electrochemical property could be ascribed to its unique hierarchical architecture, improved electronic conductivity, and robust structure.